PENGARUH KARAKTERISTIK DIREKTUR UTAMA TERHADAP PENGUNGKAPAN CORPORATE SOSIAL RESPONSIBILITY (CSR) STUDI PADA PERUSAHAAN BUMN - AZMIDA L. KWALOMINE (JURNAL RISET TERAPAN AKUNTANSI, 2017)
This study exmined the characteristics of Presiden Director and consistency in Corporate Social Responsibility(CSR) action, wich in State Owned Enterprises known as Partnership and Comunity Development Program. The purpose  of  this  study  was  to  examine  the  influence  of  President  Director  Characterisics  on  the  quality  ofPartnership and Comunity Development Program. this study used the characteristic of President Director is, education, age, tenure, and experience. The sample of this study are state owned enterprises with the total population are 119 firms, based on the sampling criteria, the final sample of this study are 50 firms. Content analysis method was used to measure the quality of Partnership and Comunity Development Program. Data wasanalysed by SPSS program. Multiple linear regression model was used to test the hypothesis. The result shows that education, age, tenure, and experience have insignificant effect toward the quality of Partnership and Comunity Development Program. Future research could investigate other variables that could affect the quality of Partnership and Comunity Development Program.